Non-discretionary resource allocation as political investment: evidence from Ghana. Issue 1 (2nd February 2017) - Asunka, Joseph
ABSTRACT: When would politicians reduce or eliminate their own discretion in the distribution of valued benefits to voters? I argue that the answer lies in the extent of partisan attachments among voters: politicians would be more likely to adopt non-discretionary or self-binding resource allocation rules in contexts where voters evince weak attachment to political parties. Non-discretionary distributive rules allow politicians to reach unattached voters with benefits without angering their loyal supporters who might otherwise expect to be favoured. They also signal politicians' commitment to unbiased distribution of public resources, which, research shows, attracts unattached voters. Analysis of data on allocations of legislators' development funds in Ghana provides strong support for this argument. This result is robust to controls for alternative explanations and thus advances understanding of when politicians in new democracies would pursue reforms designed to reduce or eliminate political discretion.